Use of modern technologies for combat units preparation and management - Drozd, Jan; Flasar, Zdenek; Stodola, Petr (Vojnotehnički glasnik / Military Technical Courier, 2017)
The paper discusses possible applications and benefits of modern technology in the preparation and management of operations (activities, combat activities). In the process of preparations and operations management, combat modeling plays an important role within the activities of military commanders and their staff. Standard combat modeling could be incorporated into the collaboration management of all components. At the staff level, the combat modeling is considered as a war game, which is part of optimal variant selection and confirmation of friendly forces action.